Are data available for tracking progress on nutrition policies, programs, and outcomes in Bangladesh? - Jangid, Manita; Neupane, Sumanta; Scott, Samuel P.; Nguyen, Phuong Hong; Kim, Sunny S.; Murira, Zivai; Torlesse, Harriet; Menon, Purnima (International Food Policy Research Institute, 2021)
The World Health Organization (WHO) and other global nutrition and health agencies recommend nutrition actions throughout the life-course to address malnutrition in all its forms. In this report, we examine how Bangladesh’s nutrition policies and programs address recommended nutrition actions, determinants, and outcomes. We review population-based surveys to assess the availability of data on nutrition actions, nutrition outcomes, and determinants of these outcomes; we also assess the data availability in administrative data systems for selected nutrition actions and outcomes. Our review identified a total of 53 recommended evidence-based nutrition actions; of these, 51 were applicable to Bangladesh, and 47of those were addressed in the country’s nutrition policies and programs. Nutrition actions that were not included in current policies and programs were: deworming during preconception and advice on consuming calcium during pregnancy. In terms of the two nutrition actions targeting early childhood, food supplementation and iron and folic acid (IFA) supplementation were not addressed by either policies or programs. National strategies and plans recognized and aimed to address all key determinants of nutrition; they also expressed an intent to address all Sustainable Development Goal (SDG) nutrition targets for maternal, infant, and young child nutrition. The Global Nutrition Monitoring Framework (GNMF) targets related to underweight among non-pregnant women 15 to 49 years and overweight among school children and adolescents five to 19 years were not addressed in the national strategies. Of the 47 actions that Bangladesh’s policies and programs address, our data review indicated that population-based surveys contained data on only 19 actions. However, of the 29 selected actions reviewed in the administrative data system, data was available only 24 actions. Data was not available from population-based surveys on a number of indicators, including to the following: IFA supplementation and deworming during adolescence; IFA supplementation during preconception; indicators focused on pregnant women including calcium supplementation, deworming, and counseling during pregnancy; indicators aimed at the postnatal period including breastfeeding support, optimal feeding of low-birth-weight infants, IFA supplementation, and food supplementation; indicators targeting early childhood including counseling on breastfeeding, counseling on complementary feeding, iron-containing micronutrient powder (MNP), growth monitoring, counseling on nutritional status, identification of severe or moderate underweight, and inpatient management of severe acute malnutrition (SAM). Administrative data systems did not contain data on counseling on exclusive breastfeeding during pregnancy, assessment of birth weight, breastfeeding support, optimal feeding of low-birth-weight infants and counseling of mothers on Kangaroo Mother Care (KMC) during pregnancy. Population-based surveys contained data on most indicators related to immediate and underlying determinants of undernutrition. In terms of outcomes related to children under five, administrative data systems and population-based surveys contained data on low birthweight, stunting, wasting, underweight, and overweight; for adolescents 11 to 19 years and non-pregnant women they contained data only on underweight. Data was available on overweight, hypertension and diabetes among adults in population-based surveys. Population based survey did not collect data on anemia among women and children. In conclusion, Bangladesh’s landscape for nutrition is robust; however, the gaps in data availability for tracking progress on nutrition are much greater than the gaps in the policies and programs that are designed to address the recommended actions. Future population-based surveys and future modifications of other data systems should aim to fill the identified data gaps for nutrition actions and few indicators under nutrition outcomes.